Chronic hyponatremia based on maxillary sinus mass. (2nd September 2021) - Tudor, Darija; Kolombo, Iva; Tot, Ana; Cikojevic, Drasko; Simunovic, Marko; Skrabic, Veselin
Abstract : Summary: This is a case report of a child with chronic hyponatremia due to the syndrome of inappropriate antidiuretic hormone secretion (SIADH) as a paraneoplastic manifestation of olfactory neuroblastoma (OFN). We hereby report a clinical presentation as well as a pragmatic approach to one of the most common electrolytic disorders in the pediatric population and have emphasized the necessity of involving the sinonasal area in the diagnostic procedure while evaluating possible causes of SIADH. This report indicates that the chronicity of the process along with the gradual onset of hyponatremia occurrence is responsible for the lack of neurological symptoms at the moment of disease presentation. Learning points: Hyponatremia is not infrequently attributed to SIADH. Paraneoplastic syndromes are uncommon but they should be considered in the differential diagnosis of pediatric SIADH. Chronic insidious hyponatremia may not be associated with clear neurological symptoms despite its severity.